2020
DOI: 10.1007/s11192-020-03800-2
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the future of library and information science and its sub-fields

Zehra Taşkın

Abstract: Forecasting is one of the methods applied in many studies in the library and information science (LIS) field for numerous purposes, from making predictions of the next Nobel laureates to potential technological developments. This study sought to draw a picture for the future of the LIS field and its sub-fields by analysing 97 years of publication and citation patterns. The core Web of Science indexes were used as the data source, and 123,742 articles were examined in-depth for time series analysis. The social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…The same is true for the "Physics, Applied" WoSSC-which, for example, contains papers of Nuclear and Condensed, two other subfields with different research trends. That is, our classification results can provide better support for the calculation of normalized citation metrics within each subfield, an issue of growing interest in Scientometrics (Pech & Delgado, 2020, 2021; consequently, they provide more accurate and reliable academic performance evaluations of researchers and institutions-for financial, strategic or Human Resource management purposes.…”
Section: Discussionmentioning
confidence: 93%
“…The same is true for the "Physics, Applied" WoSSC-which, for example, contains papers of Nuclear and Condensed, two other subfields with different research trends. That is, our classification results can provide better support for the calculation of normalized citation metrics within each subfield, an issue of growing interest in Scientometrics (Pech & Delgado, 2020, 2021; consequently, they provide more accurate and reliable academic performance evaluations of researchers and institutions-for financial, strategic or Human Resource management purposes.…”
Section: Discussionmentioning
confidence: 93%
“…While SCIM publishes 12 issues and almost 350 articles per year, the average number of articles for other journals are 156 for JASIST , 76 for JDOC , 75 for JOI , 73 for OIR and 45 for ASLIB . Also, the selected journals serve different sub-fields of information science (Taşkın, 2021a , 2021b ) and it makes the comparison difficult. To handle this problem, we provided statistics for each journal separately.…”
Section: Methodsmentioning
confidence: 99%
“…The codes were written using Python to get publications’ timeline data automatically from journal websites (Taşkın, 2021a , 2021b ). After getting the timeline data from journal websites, the publication time for each article was calculated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, researchers and academics are key players in this context and government authorities should take actions and decisions based on the results and recommendations of its researchers to achieve the SDGs in coming years [3]. According to Taşkın et al [11], they indicated that the number of publications and citations will increase each year unless there is a change in research evaluation systems.…”
Section: Introductionmentioning
confidence: 99%